Development of variable voltage variable frequency drive system for induction motor speed control - Tan, Lorinna Mei Hua (2021)
This project describes the development of a Variable Voltage Variable Frequency (VVVF) system that controls the speed of Induction Motor (IM) at specific speed. Texas Instrument C2000 Microcontroller (TMS320F28335) has been used in this project as the interface between the control design with the IM. The Texas Instrument microcontroller has been combined with the MATLAB/Simulink and the VVVF system as the communication interface for processing the speed control system. The combination between power electronic circuits and microcontroller along with variable voltage variable frequency (VVVF) technique is able to control the target speed of IM. The target value of VVVF is implemented inside Lookup table and has been combined with the Proportional Integral (PI) speed control that generates the signal into the sinusoidal pulse width modulation (SPWM) for inverter operation. The SPWM signal is produced from the microcontroller with the instruction from MATLAB/Simulink, where the controller performs the output of the motor speed. The PI speed control receives the output of a closed loop feedback system from the motor speed and the error signal is reduced to achieve the value of desired speed reference. In the conclusion, the VVVF closed loop system is very useful to control the desired speed of motor at different variable voltage and variable frequency value. As collected for the results, its show, the VVVF with PI speed control can achieve the actual speed for the IM at 1297rpm and 1499rpm when the reference speeds have been set at 1300rpm and 1500rpm respectively. At the end it can be concluded that the VVVF combined with microcontroller have created an ecosystem for speed control that have achieved the objectives.